Nanoformulation of Talazoparib Increases Maximum Tolerated Doses in Combination With Temozolomide for Treatment of Ewing Sarcoma - Baldwin, Paige; Likhotvorik, Rostislav; Baig, Nabeela; Cropper, Jodie; Carlson, Ruth; Kurmasheva, Raushan; Sridhar, Srinivas (Frontiers in Oncology, 2019)
The Pediatric Preclinical Testing Program previously identified the PARP inhibitor talazoparib (TLZ) as a means to potentiate temozolomide (TMZ) activity for the treatment of Ewing sarcoma. However, the combination of TLZ and TMZ has been toxic in both preclinical and clinical testing, necessitating TMZ dose reduction to ~15% of the single agent maximum tolerated dose. We have synthesized a nanoparticle formulation of talazoparib (NanoTLZ) to be administered intravenously in an effort to modulate the toxicity profile of this combination treatment. Results in Ewing sarcoma xenograft models are presented to demonstrate the utility of this delivery method both alone and in combination with TMZ. NanoTLZ reduced gross toxicity and had a higher maximum tolerated dose than oral TLZ. The dose of TMZ did not have to be reduced when combined with NanoTLZ as was required when combined with oral TLZ. This indicated the NanoTLZ delivery system may be advantageous in decreasing the systemic toxicity associated with the combination of oral TLZ and TMZ.